Measurement of V 0 production ratios in pp collisions at √s=0.9 and 7 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; et al. (Journal of high energy physics, 2011)
The Λ¯/Λ and Λ¯/K0S production ratios are measured by the LHCb detector from 0.3 nb−1 of pp collisions delivered by the LHC at s√=0.9 TeV and 1.8 nb−1 at s√=7 TeV. Both ratios are presented as a function of transverse momentum, p T, and rapidity, y, in the ranges 0.15 < p T < 2.50 GeV/c and 2.0 < y < 4.5. Results at the two energies are in good agreement as a function of rapidity loss, ∆y = y beam − y, and are consistent with previous measurements. The ratio Λ¯/Λ, measuring the transport of baryon number from the collision into the detector, is smaller in data than predicted in simulation, particularly at high rapidity. The ratio Λ¯/K0S, measuring the baryon-to-meson suppression in strange quark hadronisation, is significantly larger than expected.
Im Titel ist die Zahl 0 hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
*The LHCb collaboration: R. Aaij, S. Bachmann, A. Bien, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, K. Holubyev, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und sehr viele weitere Personen]
Gesehen am 16.02.2022